The influence of interest and understanding of housing developers on gated communities development - Ainur Zaireen Zainudin, 1979-; Khadijah Hussin; Fakulti Geoinformasi dan Harta Tanah (2013)
Thesis (Ph.D (Pentadbiran dan Pembangunan Tanah)) - Universiti Teknologi Malaysia, 2013